Bien estar de gallinas ponedoras y la osteoporosis (Research, Society and Development, 2020)
The objective of this review aspects concerned with the natural behavior of birds, the stress suffered when subjected to confinement, the importance of the study of the mineral bone density and the understanding of the causes of osteoporosis and appropriate measures to be taken to mitigate the severity of this disease and contribute to animal welfare. Therefore, the importance of research in the area of bone mineralization, adaptations to the environment and diets with adequate levels of calcium, vitamin D and phosphorus for maintenance of the quality of the bone tissue of birds is seen.